(untitled) (Baghdad Science Journal, 2025)
The change in the optical band gap and optical activation energy have been investigated for pure Poly (vinyl alcohol)and Poly (vinyl alcohol) doped with Aluminum sulphate to proper films from their optical absorption spectra. The absorption spectra were measured in the wave range from (200-700) nm at temperature range (25-140) 0C. The optical band gap (Eg) for allowed direct transition decrease with increase the concentration of Aluminum sulphate. The optical activation energy for allowed direct transition band gap was evaluated using Urbach- edges method. It was found that ?E increases with increasing the concentration of Al2 (SO4)3 and decreases when temperature increases.